Quentin Meillassoux: An exploration of the science-fiction extro and its implication for the science fiction literary genre - Fatha, Dias Nashrul (Abjad Journal of Humanities & Education, 2024)
Hume's problem is a philosophical problem that is still controversial today. Hume asked what guarantees and assures us that the laws of physics will continue to apply in the future. Philosophers such as Immanuel Kant and Karl Popper explored Hume's problem in several ways. However, for Quentin Meillassoux, Kant and Popper's solutions do not answer the core of Hume's problem. He explained that there are two kinds of representations in seeing the response to this problem: the representation of science fiction and extro-scientific fiction. In his work, Meillassoux examines the arguments individually and offers solutions to the possibility of the extro-scientific fiction genre in literature. This article aims to review Meillassoux's book entitled Science Fiction and Science-Extro Fiction. This study uses a textual analysis method on Meillassoux's work entitled Science Fiction and Science-Extro Fiction. The results of the analysis of this article reveal that extro-scientific fiction can be distinguished by genre from science fiction within Meillassoux's framework of thought. What is expected from Meillassoux's explanation in this article is to discuss extra-scientific fiction as an alternative medium for thinking about the future full of possibilities.